Sikap pengguna terhadap perbankan mudah alih: Kajian di kalangan kakitangan Universiti Utara Malaysia - Norfadhilah, Jauhari (2016)
The use of mobile banking as a channel that offers various financial services has become a new phenomenon in the banking industry in Malaysia. The aim of this study is to determine the level of consumer acceptance of mobile banking technology in Malaysia, which is a country with a thriving economy. Besides, this study uses the Technology Acceptance Model (TAM) and applies it to the users in Malaysia. In a sample of 380 employees that working at Universiti Utara Malaysia (UUM), the finding show that attitudes towards the use of mobile banking is influenced by the notion that mobile banking is usefulness, ease of use, enjoyment and credibility. The findings also showed that perceived usefulness, perceived ease of use, perceived enjoyment and perceived credibility have a positive and significant influence on the formation of consumer attitudes towards mobile banking. Other than that, the carried out regression analysis showed that all of these factors contributing 50 percent of the variation in consumer attitude towards mobile banking. The implications of the theoretical and practical as well as suggestions for future research are also discussed in this study.